Comparative thermogravimetric analyses of co-combustion of textile dyeing sludge and sugarcane bagasse in carbon dioxide/oxygen and nitrogen/oxygen atmospheres: Thermal conversion characteristics, kinetics, and thermodynamics. (May 2018) - Xie, Wenhao; Wen, Shaoting; Liu, Jingyong; Xie, Wuming; Kuo, Jiahong; Lu, Xingwen; Sun, Shuiyu; Chang, Kenlin; Buyukada, Musa; Evrendilek, Fatih
Highlights: Co-combustion of textile dyeing sludge and sugarcane bagasse was assessed. Co-combustion performance was improved by increased oxygen concentration. Thermodynamic parameters (Δ H, Δ S and Δ G ) and activation energy were estimated. The most efficient atmosphere for co-combustion was CO2 /O2 (7/3) atmosphere. Abstract: Thermodynamic and kinetic parameters of co-combustion of textile dyeing sludge (TDS) and sugarcane bagasse (SB) were studied using thermogravimetric analysis in CO2 /O2 and N2 /O2 atmospheres. Our results showed that the comprehensive combustion characteristic index ( CCI ) of the blends was improved by 1.71–4.32 times. With the increased O2 concentration, co-combustion peak temperature decreased from 329.7 to 318.2 °C, with an increase in its maximum weight loss rate from 10.04 to 14.99%/min and its CCI by 1.31 times ( β  = 20 °C·min −1 ). To evaluate the co-combustion characteristics, thermodynamic and kinetic parameters (entropy, Gibbs free energy and enthalpy changes, and apparent activation energy) were obtained in the five atmospheres. The lowest apparent activation energy of the TB64 blend was obtained in oxy-fuel atmosphere (CO2 /O2  = 7/3).